Designing Model of Integrated Land Waqf and Cash Waqf Empowerment in Providing Apartments: Potentials and Challenges - Anggraini, Diana Herlin Widiastuti; Rohim, Ade Nur (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to design a model for integrating waqf land and cash waqf in the provision of apartments for low-income communities in Indonesia as a solution to enhance community welfare. This study employs a qualitative research method with a literature review approach. The research indicates that the model for integrating waqf land and cash waqf holds significant potential in providing apartments for low-income communities. Waqf land, often neglected and primarily allocated for consumptive sectors, can be optimized for productive sector development through this integration. Waqf land is viewed as a strategic physical asset, while cash waqf offers flexibility in financing infrastructure development. The integration of both presents great opportunities to create sustainable social and economic impacts, with rental income from apartments serving as a productive investment that supports further development. The study also identifies several challenges related to the integration of waqf land and cash waqf, particularly concerning waqf management, which requires transparent governance, adequate regulatory support, and cross-sector collaboration. Additionally, social constraints related to public perception of waqf may also affect the implementation of this model. This research recommends innovative policies and synergy between the government, waqf institutions, and the private sector to address these challenges and maximize the potential of waqf integration in providing housing for those in need.